The fifth wave : the evolution of American higher education / Michael M. Crow and William B. Dabars. - Crow, Michael M.; Dabars, William B. (Johns Hopkins University Press, 2020)
"Building on the success of Designing the New American University (JHUP, 2015), this book examines the historical development of American higher education (in four preceding waves: colonial colleges, universities state universities, land-grant universities, research) and then describes the emerging next wave of institutions that will transform the field. What emerges in this fifth wave of universities, of which ASU is an exemplar, are institutions responsive to the needs of students, committed to access, regionally embedded, and focused on solving global problems interdisciplinarily"-- Provided by publisher.
Keywords: Education, Higher -- Aims and objectives -- United States.; Universities and colleges -- United States -- Administration.; Education, Higher -- Aims and objectives.; Universities and colleges -- Administration.; United States.